Overexpression miR‐24‐3p repressed Bim expression to confer tamoxifen resistance in breast cancer. Issue 8 (18th April 2019) - Han, Xu; Li, Qiaobei; Liu, Chang; Wang, Chunyan; Li, Yinyan
Abstract: Endocrine therapy resistance represents a major challenge to the successful treatment of patients with breast cancer. The development of tamoxifen resistance commonly occurrs during the treatment of patients with breast cancer whereas its underlying mechanisms remain elusive. Here, we found that miR‐24‐3p regulated tamoxifen sensitivity in breast cancer cells. Forced overexpression of miR‐24‐3p augmented tamoxifen‐induced cell viability inhibition in breast cancer cells, while knockdown of miR‐24‐3p partially attenuated the cytotoxicity effect of tamoxifen. Moreover, we discovered Bim as a target gene of miR‐24‐3p in breast cancer cells by RNA immunoprecipitation, quantitative reverse transcription polymerase chain reaction, Western blot, and dual luciferase reporter assay. In our established tamoxifen resistant MCF7 cell line (MCF7/TAM), there was a significant elevation of miR‐24‐3p and decrease of BIM expression compared with parental MCF7 cells. In addition, the inhibition of miR‐24‐3p could reverse the tamoxifen resistance of MCF7/TAM cells by the induction of cell apoptosis. Silencing of Bim expression blocked miR‐24‐3p inhibitor–induced elevation of tamoxifen sensitivity of MCF7/TAM cells. Using tumor tissues from patients with breast cancer, we also found that the expression of miR‐24‐3p was negatively correlated with Bim mRNA expression. Collectively, our study highlighted the pivotal role of miR‐24‐3p overexpression in mediating the development of tamoxifen resistance in breast cancer and suggested miR‐24‐3p might be a predictor or target for patients with breast cancer. Abstract : miR‐24‐3p overexpression is involved in the development of tamoxifen resistance in breast cancer through repression of Bim.